Beyond the decision to ally: Constraints on adapting to emergent control risks. (September 2021) - Sutton, Nicole; Brown, David A.
Abstract: Partners' efforts to manage risk extend far beyond decisions made when an alliance is formed and continue throughout its lifecycle. As an alliance matures, it is expected that partners will adapt controls to address unanticipated, emergent risks; however, empirical evidence indicates that such changes are relatively rare. This study aims to advance our understanding of the constraints on control adaptation by examining the role of governance inseparability, a condition in which partners' prior control choices limit the range and types of subsequent strategic control options. Using a longitudinal analysis of two mature alliances, we examine episodes where partners struggled to switch from or differentiate alliance controls compromised by emergent risks. We trace these constraints to a range of sources, including contractual commitments, alliance-specific regulation, and control consistency. Furthermore, we observe how partners introduced 'compensatory controls', that is, additional controls to remedy secondary control problems created by the existing control infrastructure.